New algorithm method for solving the variational inequality problem in Hilbert space - Hussein Maibed, Zena (Global Journal of Mathematical Analysis, 2019)
Theipurpose of,thisipaper,is toiintroduce,aiconcept of generalizedinon_spreading,and define a new algorithm,for infinite,families of generalizedinon_spreading,and finite families of resolvent,mappings. Also, We study,the existence,solution of variational inequality,to a commonifixedipoint in Hilbertispaces. The main,results in this paper extendiand generalized,of many knowniresults initheiliterature.Â Â